Functional Scaffolding for Brain Implants: Engineered Neuronal Network by Microfabrication and iPSC Technology - Shimba, Kenta; Chang, Chih-Hsiang; Asahina, Takahiro; Moriya, Fumika; Kotani, Kiyoshi; Jimbo, Yasuhiko; Gladkov, Arseniy; Antipova, Oksana; Pigareva, Yana; Kolpakov, Vladimir; Mukhina, Irina; Kazantsev, Victor; et al. (Frontiers in Neuroscience, 2019)
Neuroengineering methods can be effectively used in the design of new approaches to treat central nervous system and brain injury caused by neurotrauma, ischaemia or neurodegenerative disorders. During the last decade, significant results were achieved in the field of implant (scaffold) development using various biocompatible and biodegradable materials carrying neuronal cells for implantation into the injury site of the brain to repair its function. Neurons derived from animal or human induced pluripotent stem (iPS) cells are expected to be an ideal cell source, and induction methods for specific cell types have been actively studied to improve efficacy and specificity. A critical goal of neuro-regeneration is structural and functional restoration of the injury site. The target treatment area has heterogeneous and complex network topology with various types of cells that need to be restored with similar neuronal network structure to recover correct functionality. However, current scaffold-based technology for brain implants operates with homogeneous neuronal cell distribution, which limits recovery in the damaged area of the brain and prevents a return to fully functional biological tissue. In this study, we present a neuroengineering concept for designing a neural circuit with a pre-defined unidirectional network architecture that provides a balance of excitation/inhibition in the scaffold to form tissue similar to that in the injured area using various types of iPS cells. Such tissue will mimic the surrounding niche in the injured site and will morphologically and topologically integrate into the brain, recovering lost function.